Parental stress and quality of life among parents with hearing impaired child and non hearing impaired child - Ling, Wong Yee (Universiti Sains Malaysia, 2015)
Parents are affected when their child is diagnosed with hearing loss. Hearing loss in children will affect parental stress and their quality of life as well. The objective of this study was to examine the differences of the parental stress and quality of life among parents with hearing impaired child and parents with non hearing impaired child from the age of 2 to 6 years old. This study also aims to examine the correlation between parental stress and quality of life among both groups of parents. The participants consisted of two groups; study group and control group. The study group is those parents who send their hearing impaired child for further management with audiologist at Audiology Clinic, Hospital Universiti Sains Malaysia, D’KECEK and also further management with Speech Language Pathologist at Klinik Pertuturan Bahasa, School of Health Sciences, Universiti Sains Malaysia, and Speech Clinic at Hospital Universiti Sains Malaysia. The control group was those parents having children with normal hearing who will be randomly collected from a preschool named “Prasekolah Sekolah Kubang Kerian 3” at Kubang Kerian, Kelantan. For each group, the total participants were also 32 parents (16 mothers and 16 fathers). The data obtained were analysed using independent-T test and Pearson Product Moment Correlation Coefficient. The result indicated that there was significant difference on parental stress among mothers with hearing impaired child and mothers with non hearing impaired child (p value<.05). However, there was no significant difference on parental stress among fathers with hearing impaired child and fathers with normal hearing child (p value >.05). The results showed no significant difference on psychological, physical and social domains of quality of life among mothers with hearing impaired child and mothers with non hearing impaired child. However, the statistical analyses indicated that there was a significant different on environment domain of quality of life among mothers of both groups. For fathers, there was no significant difference on all domains of quality of life among them. This study provides some ideas on parental stress and quality of life among parents with hearing impaired and non hearing impaired child. These informations were important for professionals such as Speech Language Pathologist. The informations help as a guideline for them to understand more about parental stress and quality of life especially among parents of hearing impaired child. This can help the clinicians to provide the suitable advises and counseling to the parents in terms of increasing parenting skills and quality of life as well.